2009
DOI: 10.1080/02772240802607394
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four methods for the extraction of lipopolysaccharide from cyanobacteria

Abstract: Four procedures were compared for the extraction of lipopolysaccharide (LPS) from 10 laboratory strains of cyanobacteria. LPS yields as a percentage of cyanobacterial dry weight ranged from 0.03 to 6.13. The heterotrophic bacterial LPS marker 2-keto-3-deoxyoctonoic (KDO) acid was not detectable in any of the cyanobacterial LPS preparations. All methods yielded LPS that contained biologically-and toxicologically-significant quantities of the cyanotoxin microcystin, when applied to some, but not all, microcystin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…LPS were found to account for up to 4.1% of the dried biomass weight ( Table 1 ). In general agreement with prior studies of heterotrophic bacterial [ 28 ] and cyanobacterial [ 29 ] LPS, considerable variation in extraction yield (0.1–4.1%) between Microcystis strains was observed ( Table 1 ). In fact, LPS from an additional sub-tropical Microcystis isolate were prepared, but yielded too little for subsequent experimental studies (data not shown).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…LPS were found to account for up to 4.1% of the dried biomass weight ( Table 1 ). In general agreement with prior studies of heterotrophic bacterial [ 28 ] and cyanobacterial [ 29 ] LPS, considerable variation in extraction yield (0.1–4.1%) between Microcystis strains was observed ( Table 1 ). In fact, LPS from an additional sub-tropical Microcystis isolate were prepared, but yielded too little for subsequent experimental studies (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the alternative mechanism suggested here ( i.e. , interaction with glutathione-based pathways), specifically in relation to previously identified differences between heterotrophic and cyanobacterial LPS chemical composition (e.g., lipid A and lack of Kdo; [ 29 , 33 ]), and between mammalian and teleost fish systems ( i.e. , absence of TLR4 in the latter; [ 19 ]), more generally indicates a possibly novel toxicophore for cyanbacterial LPS in teleost fish.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…For more than 100 years, the use of bacterial endotoxins (or LPSs) has been an interesting and enigmatic subject of investigation [ 13 ]. Despite the widespread use of various methods for LPS extraction, all of the methods are characterized by several limitations, such as the use of reagents that degrade LPSs [ 14 ], inapplicability at a low scale [ 9 ], and the absence of data regarding the structure of the extracted LPSs and the content of their impurities [ 10 , 11 ]. Additionally, extraction methods are often highly complex and time-consuming.…”
Section: Resultsmentioning
confidence: 99%
“…However, these methods are difficult to apply when only a small amount of bacterial biomass is available. For example, Lindsay et al [ 9 ] previously showed that the Westphal or Darveau methods may produce a relatively low yield of LPSs. Additionally, to date, several methods that are applicable for the microscale extraction of LPSs have been developed, such as the method of extracting LPSs by boiling [ 10 ], the method of extracting LPSs by using phenol and guanidine thiocyanate [ 11 ], and the method of extracting LPSs by boiling with SDS and subsequent digestion by proteinase K, which was described by Hitchcock et al [ 12 ].…”
Section: Introductionmentioning
confidence: 99%